Guddappa Harijan of Hanagal Taluk, Bombay Karnataka’s Silent Revolution of Harijanodhara - Hemappa B. Kenchalli, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Gandhiji’s Harijanoddhara (upliftment of the untouchables) movement played a crucial role in India’s freedom struggle, as he believed that true independence was impossible without eradicating untouchability. Inspired by Gandhiji’s call, many reformers and freedom fighters in Karnataka, particularly in Haveri district, actively participated in this social revolution. Couples like Mrs. Nagamma Patil and Veeranagowda of Kachavi village, supported by leaders such as K.F. Patil, T.R. Nesvi, Hallikeri Guddeppa, Sanguru Kariappa, and Menasinal Thimmanagoudru, advanced the cause through institutions like Mahila Vidya Peetha, Hubballi. Local leaders including Nyamati Veerabhadrappa and Betageri Ramanna also led community initiatives to abolish caste discrimination. Significantly, Guddanagouda Neelanagouda Patil (Harijan) of Akkialuru village emerged as a symbol of Gandhian ideals, dedicating his life to the upliftment of his community. His lifelong struggle, continuing until his passing in 2018, exemplifies the spirit of Gandhiji’s Harijan movement in Karnataka’s freedom and social reform efforts.
Keywords: Gandhiji; Harijanoddhara; Haveri district; untouchability; social reform; Karnataka freedom movement